Project HOPE: Evaluation of Health Science Career Education Programming for Rural Latino and European American Youth. Issue 1 (March 2017) - Ali, Saba Rasheed; Brown, Samantha Danielle; Loh, Yunkyoung
Abstract : Project HOPE comprises a health science career pipeline program based in social cognitive career theory. The program aims to promote health science career exploration for rural and Latino middle school students while simultaneously emphasizing the importance of achieving in math and science subjects. The authors conducted 2 studies to evaluate Project HOPE using baseline and follow‐up evaluation data. Results of Study 1 indicated that Project HOPE was associated with increases in math/science self‐efficacy for both Latino ( n = 42) and European American ( n = 31) students. Results of Study 2 indicated that Project HOPE was associated with higher health science career self‐efficacy beliefs for European American students ( n = 22) and higher health science career interests for Latino students ( n = 28). These results suggest that domain‐specific career interventions for middle school students that focus on jobs tied to the local economy may be a useful way to engage students in career exploration.